The value of cuproptosis-related differential genes in guiding prognosis and immune status in patients with skin cutaneous melanoma - Sun, Yuming; Lei, Shaorong; Luo, Xiangyue; Jiang, Chufeng; Li, Zhexuan (Frontiers in Pharmacology, 2023)
Background: Skin cutaneous melanoma (SKCM) is one of the most malignant tumors, and its incidence is increasing. Cuproptosis is a new type of programming cell death recently reported, which may play an important role in SKCM. Method: The mRNA expression data of melanoma were gathered from the TCGA and GEO databases. We constructed a prognostic model based on cuproptosis-related differential genes in SKCM. Finally, real-time quantitative PCR was performed to verify the expression of cuproptosis-related differential genes in patients with different stages of cutaneous melanoma. Results: We detected 767 cuproptosis-related differential genes based on 19 cuproptosis-related genes, and screened out 7 differential genes to construct a prognostic model, which including three high-risk differential genes (SNAI2, RAP1GAP, BCHE), and four low-risk differential genes (JSRP1, HAPLN3, HHEX, ERAP2). Kaplan-Meier analysis showed that SKCM patients with low-risk differential genes signals had a better prognosis. The KEGG results manifested that cuproptosis-related differential genes are mainly involved in T cell receptor signaling pathway, chemokine signaling pathway, natural killer cell mediated cytotoxicity, B cell receptor signaling pathway, T cell receptor signaling pathway. In our risk scoring model, the 1-year, 3-year and 5-year ROC values were 0.669, 0.669 and 0.685, respectively. Moreover, the tumor burden mutational and immunology function, cell stemness characteristics and drug sensitivity have significant differences in low-risk groups and high-risk groups. The mRNA expression level of SNAI2, RAP1GAP and BCHE in stage Ⅲ+Ⅳ SKCM patients was significantly higher than that in stage Ⅰ+Ⅱ patients, while the expression of JSRP1, HAPLN3, HHEX and ERAP2 in stage Ⅰ+Ⅱ SKCM patients was significantly higher than that in stage Ⅲ+Ⅳ SKCM patients. Conclusion: In summary, we suggest that cuproptosis may play an important role in regulating the tumor microenvironment and prognosis of SKCM patients, and may provide a theoretical basis for SKCM patients survival studies and clinical decision-making with potentially therapeutic drugs.